The Determinants of Trust: Evidence from Rural South India - Anne Hilger; Christophe Jalil Nordman (Institute of Labor Economics (IZA), 2020)
Trust and participation in social networks are inherently interrelated. We make use of India's demonetization policy, an unexpected and unforeseeable exogenous variation, to causally identify the effect of social networks in determining trust. We use first-hand quantitative and qualitative data from rural South India and control for individual characteristics (personality traits, cognitive ability) that could influence network formation and trust, finding that social interactions have a significant effect on trust among men, as well as across castes. Among lower castes, who live in homogeneous neighborhoods and relied on neighbors and employers to cope, extending one's network lowers trust in neighbors. Among middle castes, who live in more heterogeneous neighborhoods and relied predominantly on other caste members, a larger network size leads to greater trust placed in kin among employees but lesser in neighbors. This paper thus shows that social interactions can foster trust and highlights the importance of clearly defining in- and out-groups in trust measures within highly segregated societies.
Keywords: O12; D85; D91; 330; India; trust; social networks